Antibiotic efficacy and resistance patterns of urinary tract infection-causing bacteria in dogs and resistome of multidrug-resistant Klebsiella pneumoniae via whole genome sequencing in South Korea - Lee, Da-Eun; Hyeon, Ji-Yeon; Kang, Seok-Won; Lee, Dong-Yeop; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2024)
Bacterial urinary tract infections (UTIs) are prevalent in dogs and necessitate antibiotic intervention. However, the emergence of multidrug-resistant (MDR) bacteria poses significant challenges to antibiotic therapy. Although fosfomycin has been demonstrated to achieve and maintain high concentrations in urine, suggesting its potential for treating UTIs in dogs, its efficacy and the resistance profiles of urinary pathogens from canine UTIs remain elusive. Therefore, this study was conducted to investigate the antibiotic susceptibility of bacterial pathogens isolated from companion dogs with UTIs, with a particular focus on their susceptibility and resistance to fosfomycin. A total of 70 isolates from urine samples were analyzed, of which Escherichia coli (n = 18), Proteus mirabilis (n = 9), Klebsiella pneumoniae (n = 5), and Staphylococcus pseudintermedius (n = 5) were predominant. Resistance to erythromycin was most prevalent (94.59%), followed by clindamycin (91.89%) and ampicillin (78.37%), whereas the lowest resistance rate was observed for amikacin (5.40%). Resistance to fosfomycin was observed in 15 out of the 37 predominant isolates (40.54%), including all K. pneumoniae isolates (100%). All isolates, except 4 E. coli strains, were categorized as MDR (33 out of 37; 89.18%). The resistance rates for amoxicillin/clavulanic acid and trimethoprim-sulfamethoxazole, which are common first-line antibiotics for canine UTIs, were 48.64 and 56.75%, respectively. Whole-genome sequencing of K. pneumoniae isolates, which exhibited high resistance to fosfomycin, revealed multiple antibiotic resistance genes, with chromosomal fosA present in all isolates. Among the 27 dogs with recurrent infection included in this study, 2 were administered fosfomycin, resulting in clinical remission, as evidenced by negative urine culture tests. Overall, this study is the first to demonstrate the importance of assessing fosfomycin resistance profile for optimal treatment of canine UTIs, particularly in cases involving MDR strains.